Synthesis and characterization of a MgNi-RE alloy for hydrogen storage. (19th October 2017) - Dell'Era, A.; Pasquali, M.; Vecchio Ciprioti, S.; Lupi, C.; Brotzu, A.; Mura, F.; Tuffi, R.
Abstract: The synthesis and characterization of a MgNi alloy having La and Ce as catalysts, have been performed. The alloy behavior was studied at given fixed temperature and pressure during hydrogen absorption/desorption tests. The La and Ce addition was carried out starting from a commercial alloy, named "Firesteel". The alloy synthesized has the following formula Mg68 Ni26 M5 X, where X represents Si and Fe impurities and M stands for the mixture of rare earths metals. The alloy has been prepared by a melting process in an induction furnace equipped with a centrifugal casting system and then grinded, by both hydraulic press and ball milling. The alloy has been characterized by SEM, BET, XRD, DSC-TGA analysis and by a mass flow measurement apparatus. The experiments on alloy sample showed that, after activation, hydrogenation occurs at 300 °C in three stages at three different pressures: 3, 4 and 7 atm, involving respectively 0.15 wt%, 0.4 wt% and 2.2 wt% of hydrogen absorbed. Reversible hydride dehydrogenation, inside the mass flow measurement apparatus, requires a working temperature of 350 °C to obtain, with remarkable reaction rate, about 2.7%, hydrogen desorption. Highlights: MgNi based alloy synthesis for hydrogen storage application has been performed. The alloy has been produced by adding "Firesteel", that contains Metal Rare Earths. Characterization by SEM, BET, XRD, DSC-TG analyses and by mass flow type apparatus. Reversible hydrogen desorption of about 2.7% with good reaction rate was obtained. The temperature desorption presenting a faster kinetic is about 350° C.